Interpretations and Claims of Chair Symbol Ideology on Tempo Magazine’s Cover, March 2024 Edition - Oda, Sukur; Hasyim, Muhammad; Ilmi, Nur; Sabata, Yusniati N. (BABASAL English Education Journal, 2024)
The research seeks to explain the ideology claim of the chair depicted in the cover of Tempo magazine on March 25-31, 2024 edition. The research method employs qualitative analysis with Roland Barthes’ semiotic approach, including denotation description, connotation interpretation, and myth/ideology claims. Data collection for this study was conducted through literature observation techniques, focusing on two cover images from the March 25-31, 2024 edition of Tempo magazine. The research reveals that the ideology represented by the chair on the magazine cover reflects human avarice within the framework of power. This ideological perspective is derived from an in-depth analysis of the chair’s characteristics in relation to human desires. Keywords: Tempo Magazine Cover; Roland Barthes; Semiotics